2019
DOI: 10.1002/fsn3.1288
|View full text |Cite
|
Sign up to set email alerts
|

Release principle of peptides and amino acids during the autolysis of shrimp head from Litopenaeus vannamei after UV‐C irradiation stress

Abstract: UV-C irradiation can activate endogenous enzymes in the body of many aquatic animals. Autolysis kinetics of shrimp head after UV-C irradiation stress was investigated.During the first 5 hr of autolysis, the release of the autolysis products was in line with the first-order equations of the reaction rate: Y = 37.681e −0.173t , Pe = −1.769Y + 74.156, and TP = −1.5117Y + 60.866. A good linear correlation was founded between the release of total protein and that of products with molecular weight of 3,000 Da after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Our previous studies have shown that endogenous enzymes play an important role in the autolysis of shrimp heads, and UV‐C irradiation had a remarkable activation effect on protease (Cao et al ., 2014; Cao et al ., 2020). Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that endogenous enzymes play an important role in the autolysis of shrimp heads, and UV‐C irradiation had a remarkable activation effect on protease (Cao et al ., 2014; Cao et al ., 2020). Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…which are found in fishery waste can hydrolyze the tissues spontaneously under certain conditions. This phenomenon is called “autolysis” (Cao et al., 2019). However, the use of endogenous enzymes for hydrolysates could have many advantages and could improve the properties of resulting peptides, since it allows the control of the hydrolysis and thus minimizes undesirable reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Cao et al. (2020) evaluated the release of peptides and amino acids during the autolysis of Pacific white shrimp heads after UV irradiation stress. The amount of free amino acids increased during autolysis, and glutamine and asparagine showed the highest increase.…”
Section: Application or Developed Technology For Production Of Hydrol...mentioning
confidence: 99%